Breakthroughs in research and treatment of early breast cancer: An overview of the last three decades - Kaufmann, M; Von Minckwitz, G; Loibl, S; Bergh, J; Conte, P; Darby, S; Eiermann, W; Howell, A; Kiechle, M; Mauri, D; Senn, H; Viale, G (2013)
Breast cancer has become curable for the majority of women in Western Europe and North America. Advances have been made in imaging diagnostics as well as the implementation of nationwide screening programmes. Nowadays, we talk about prevention as well as treatment. Pathology has moved from pure morphology (tumour type, grade and stage) to biological characterisation of the tumour. Treatment has changed considerably through a better understanding of the disease; from a local disease predominated by extensive and mutilating surgical techniques to a point where breast cancer has come into its own as a systemic disease with equal "rights" to local as well as systemic treatment. This paradigm shift has led to a multidisciplinary approach of the understanding and treatment of breast cancer. Molecular classification has changed the understanding of breast cancer and will be the basis for an even more individualised treatment. New (biological) agents will help to further tailor treatment to response or resistance. While systemic treatment has been increased in number and duration surgical/local strategies have been reduced to minimum. Evidence-based medicine has helped to improve and standardise treatment of breast cancer. This review summarises the 10th Biedenkopf meeting that was held to review the advances in breast cancer understanding and treatment. © 2013 Springer-Verlag Berlin Heidelberg.